2011
DOI: 10.1038/ajh.2011.146
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Calibration Error in the Transfer Function-Derived Central Aortic Blood Pressures

Abstract: Noninvasive application of the generalized transfer function techniques produces estimates of SBP-C and PP-C with errors equivalent to those of the oscillometric blood pressure monitor in the estimation of SBP-B and PP-B. The output errors can be predicted from input errors of SBP-O and DBP-O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 25 publications
5
53
0
Order By: Relevance
“…Similarly to aSBP, the between-method-difference of 4.6 mm Hg in aPP assessment is similar in extent with the relevant difference in bPP. These differences are in line with the results of experiments comparing different BP measuring techniques with invasive recordings, which showed that noninvasive application of generalized transfer function produces estimates of aSBP and aPP with errors similar to those inserted by oscillometric estimation of invasive bSBP and bPP [28]. It should be noted, however, that this significant difference in aPP measurements between the two devices, may suggest that they are not interchangeable in assessing this parameter, which was previously shown to be an important risk factor in ESRD patients [13].…”
Section: Discussionsupporting
confidence: 75%
“…Similarly to aSBP, the between-method-difference of 4.6 mm Hg in aPP assessment is similar in extent with the relevant difference in bPP. These differences are in line with the results of experiments comparing different BP measuring techniques with invasive recordings, which showed that noninvasive application of generalized transfer function produces estimates of aSBP and aPP with errors similar to those inserted by oscillometric estimation of invasive bSBP and bPP [28]. It should be noted, however, that this significant difference in aPP measurements between the two devices, may suggest that they are not interchangeable in assessing this parameter, which was previously shown to be an important risk factor in ESRD patients [13].…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, modelderived central systolic pressures result to be generally lower than the SphygmoCor estimations, while diastolic values are higher. Notice that if the SphygmoCor estimations were adjusted to include the bias arising from its non-invasive calibration [6,7], the errors of the mathematical model would become very small: the mean difference would be equal to 0.4 mmHg for the systolic blood pressure and 4.4 mmHg for the diastolic ones. However, such a bias correction has to be considered as a speculation, as we have no data confirming that errors affecting our central pressure estimations obtained with the SphygmoCor exhibit the same mean value (i.e., the bias) measured in the large scale tests [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The major source of error of such disappointing results may primarily arise from inaccurate cuff BP values used for calibration, as discussed in our previous study. 27 Further studies should be performed to investigate and quantify the effects of calibration errors on different methods for estimating SBP-C and central aortic pulse pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other noninvasive methods, the major source of errors arises from the decreased accuracy of sphygmomanometer-measured brachial BP. 27 The improvement in the measurement accuracy of brachial BP by automatic BP monitors would be beneficial for risk assessment not only in current management of hypertension, but also in the clinical application of central BP concepts in the near future.In a previous study that tested the validity of 2 noninvasive SBP-C measurement devices, 28 large systematic bias and …”
mentioning
confidence: 99%